2020
DOI: 10.3390/polym12081781
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Marble Waste into High-Performance, Water-Resistant, and Thermally Insulative Hybrid Polymer Composites for Environmental Sustainability

Abstract: Marble waste is generated by marble processing units in large quantities and dumped onto open land areas. This creates environmental problems by contaminating soil, water, and air with adverse health effects on all the living organisms. In this work, we report on understanding the use of calcium-rich marble waste particulates (MPs) as economic reinforcement in recyclable polypropylene (PP) to prepare sustainable composites via the injection molding method. The process was optimized to make lightweight and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
(68 reference statements)
3
15
0
Order By: Relevance
“…The residue contains aluminum oxide and salts, and the disposal in landfills can release noxious gases in the environment. Marble industry also generates marble waste powder or sludge, around 200 million tons per year worldwide, which has been recently studied as fillers into PP [ 39 ] and epoxy resin composites. [ 40 ] The authors reported a residue rich in dolomite (CaMg(CO 3 ) 2 ) and calcite (CaCO 3 ) or calcium oxides with potential to improve mechanical and thermal properties of materials in order to replace common mineral fillers.…”
Section: Industrial Residuesmentioning
confidence: 99%
“…The residue contains aluminum oxide and salts, and the disposal in landfills can release noxious gases in the environment. Marble industry also generates marble waste powder or sludge, around 200 million tons per year worldwide, which has been recently studied as fillers into PP [ 39 ] and epoxy resin composites. [ 40 ] The authors reported a residue rich in dolomite (CaMg(CO 3 ) 2 ) and calcite (CaCO 3 ) or calcium oxides with potential to improve mechanical and thermal properties of materials in order to replace common mineral fillers.…”
Section: Industrial Residuesmentioning
confidence: 99%
“…Cotana states that residual lignin from bioethanol production using Arundo donax as raw material is suitable to be used as filler in composites, as composition and thermal degradation profiles look favorable [ 56 ]. Lignin has been successfully used for the reinforcement of several matrices (PP, PE, PLA or PVA among others) [ 34 , 57 , 58 ], with applications in energy storage devices, adhesives or biosensing [ 32 ]. Moreover, Vaidya [ 59 ] has used lignin from a saccharification process in a biorefinery as a reinforcement of a PHB matrix, obtaining a composite suitable to be 3D-printed, reducing the warpage observed for neat PHB printed parts.…”
Section: Polymer Compositesmentioning
confidence: 99%
“…Waste materials can also be incorporated into polymer matrices to obtain composites with interesting properties. For example, Bakshi and collaborators [ 58 ] have obtained a lightweight material with a low thermal conductivity, which is suitable to be used in civil applications, by adding marble waste particulates into a polypropylene matrix in up to 80% weight. The incorporation of marble particles into the polypropylene matrix led to the increase of tensile and flexural strength.…”
Section: Polymer Compositesmentioning
confidence: 99%
“…Taking the concept of reinforcing construction materials with fly ash, many researchers have shown that there exists excellent compatibility between fly ash and thermoplastic polymers and developed composites of this kind [ 16 , 17 , 18 , 19 , 20 ]. Other research works have also demonstrated the benefit of using treated fly ash in a wide range of polymer matrices.…”
Section: Introductionmentioning
confidence: 99%